2018
DOI: 10.1103/physrevlett.120.135502
|View full text |Cite
|
Sign up to set email alerts
|

Atomic Dynamics in Simple Liquid: de Gennes Narrowing Revisited

Abstract: The de Gennes narrowing phenomenon is frequently observed by neutron or x-ray scattering measurements of the dynamics of complex systems, such as liquids, proteins, colloids, and polymers. The characteristic slowing down of dynamics in the vicinity of the maximum of the total scattering intensity is commonly attributed to enhanced cooperativity. In this Letter, we present an alternative view on its origin through the examination of the time-dependent pair correlation function, the van Hove correlation function… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
31
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 43 publications
(36 citation statements)
references
References 27 publications
5
31
0
Order By: Relevance
“…Since then it became customary to equate the observation of the de Gennes narrowing to the confirmation of collective excitations. A recent study [18], however, showed otherwise. It was found that even in high-temperature liquid, in which atomic motions are uncorrelated, the decay time of G(r, t) depends linearly on distance.…”
Section: Evolution With Timementioning
confidence: 88%
See 1 more Smart Citation
“…Since then it became customary to equate the observation of the de Gennes narrowing to the confirmation of collective excitations. A recent study [18], however, showed otherwise. It was found that even in high-temperature liquid, in which atomic motions are uncorrelated, the decay time of G(r, t) depends linearly on distance.…”
Section: Evolution With Timementioning
confidence: 88%
“…The data points are shown in the form of log{[τ(r)-τ 0 ]/τ r } versus log(r/r 1 ) to highlight χ from the expected power law dependence. The short dashed lines serve as guides to the eye[18].…”
mentioning
confidence: 99%
“…This effect is generally considered to be the evidence of collective excitations, but our recent results have shown otherwise. As shown in Figure 2 the decay time of the VHF increases linearly with distance, with the rate related to the Maxwell relaxation time [4]. In general the r-dependent decay time depends on r as,…”
Section: Medium-range Density Correlationmentioning
confidence: 91%
“…The VHF has been known for a long time, but only recently it became possible to determine it by inelastic scattering experiments as shown in Figure 1 [3]. At the same time the behavior of the VHF was examined by molecular dynamics (MD) simulation, which gave a new insight on the interpretation of the VHF [4]. In particular, it became clear that the dynamics of the medium-range correlations beyond the first nearest neighbors is quite distinct from that of the short-range structure represented by the first neighbor shell.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation